“Kuwentos as Resistance”: Revealing White Emotionalities in the Social Justice Leadership of Asian American Educators - Jessica Wei Huang; Cheryl E. Matias (Education Sciences)
Asian American school leaders in K-20 schools and universities remain underrepresented in the field. As such, it is imperative that we study the experience of Asian American women (AAW) leaders to understand the racialized experiences of this specific group, particularly when they enact innovative leadership. We, the authors, argue that behind these racialized experiences are white emotionalities that are imposed upon AAW in uniquely raced and gendered ways. This conceptual paper addresses the following question: “how do white emotionalities thwart the innovative social justice efforts of female Asian American leaders in K-20 education?” To answer, we drew on the “kuwentos” of two AAW school leaders: one from K-12 administration and one from higher education administration. Kuwentos is derived from the Pinay concept of storytelling; thus, it is a befitting methodology to explicate these two women’s particular racial experiences. To critically interpret invisible operations of whiteness, we employed critical race hermeneutics (CRH) to reveal what is often left to the unconscious when examining the impact of whiteness on people of Color. To reveal how these seemingly natural presumptions are not so natural, CRH must be used. In drawing attention to how white emotionalities impact the innovative leadership of AAWs, the authors first use kuwentos to tell our own stories of experiencing white emotionalities. We then analyze these kuwentos through a CRH lens and end with implications and recommendations to positively impact AAW educational leaders.